The Role of Home Literacy Environment on The Literacy Skills Enhancement Among Grade Two Learners - Jean Bardinas; Kaitlin Marie Opingo; Adrian Duites (Journal of Learning and Development Studies, 2026)
This study assessed the influence of the home literacy environment on the literacy skills of learners. It specifically examined the status of the home literacy environment in terms of physical environment, parent literacy habits, child literacy habits, parent–child interaction, and parental beliefs, as well as the learners’ literacy performance in word recognition, sentence reading, reading fluency, and comprehension. A descriptive–correlational research design was employed. Using purposive sampling, the study involved 71 respondents, composed of 69 parent–child pairs and 2 Grade Two teachers. Data were gathered through an adapted Home Literacy Environment Questionnaire and the Comprehensive Rapid Literacy Assessment (CRLA). Descriptive statistics, weighted mean, standard deviation, frequency count, percentage, and Pearson Product–Moment Correlation Coefficient were applied. Findings revealed that the home literacy environment was generally supportive, though variations existed across domains. Learners demonstrated developing literacy skills, and a statistically significant relationship was found between the home literacy environment and literacy performance. The study concluded that literacy development was strongly shaped by home conditions and parental engagement. It recommended the implementation of a Literacy Skills Enhancement Plan, focusing on improving word recognition, fluency, comprehension, and strengthening home–school collaboration.